Telaah Kebijakan Pengembangan Kompetensi Guru Oleh Pemerintah di Era Society 5.0 - Melisa Fitri, Suci; Zakia Khairani, Rohima; Ramadhani Aditha, Suhaila; Hidayatullah, Rully; Hadeli (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The era of Society 5.0 has brought significant changes to various aspects of life, including the field of education. In facing the challenges and opportunities of this era, the role of teachers as agents of change becomes increasingly strategic. Therefore, the development of teacher competencies has become a central focus in national education policies. This study aims to examine government policies related to teacher competency development within the context of Society 5.0. The method used is library research, by reviewing various literatures, policy documents, and relevant previous studies. The findings indicate that the government has designed a number of policies aimed at enhancing teacher competencies, including pedagogy, digital literacy, leadership, and instructional innovation. However, the implementation of these policies still faces several challenges, such as unequal access, resource readiness, and the need for continuous support. This study is expected to serve as a reflection as well as a contribution toward shaping more responsive and adaptive education policies for the demands of the current era.